Pengaruh Struktur Kepemilikan pada Kinerja Keuangan Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di BEI - F. Purnama, Dwinta; Muchtar, Susi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to explain the effect of the ownership structure on the financial performance of companies in the transportation and logistics sector listed on the Indonesia Stock Exchange. This research method is quantitative. The sample used in this study is the transportation and logistics sector companies listed on the Indonesia Stock Exchange for nine years from 2013 to 2021. The total number of companies for being samples is 11 companies. The results showed that the regression equation are ROAit = -1.240411it + 2.628837GOPIt + 0.388680FOPit + 1.278487IOPit + 4.157551MOPIt + 0.036448CSit and ROEit = -0.426944it + 0.728267GOPIt + 0.95709 6FOPit + 0 .757987IOPit + 0.502168MOPIt - 0.045640CSit. The conclusions drawn from this study are that institutional ownership and managerial ownership affect ROA, while state ownership, foreign ownership, and capital structure do not affect the return on assets. In addition, state ownership, foreign ownership, institutional ownership, managerial ownership, and capital structure do not affect the return on equity.